Diversity of Arthropods in Peanut Plants (Arachis hypogaea L) Administered Using Organic Fertilizer in Dry Land - Dessy Astuti; Neni Marlina; Maria Lusia; Ika Paridawati; Joni Philep Rompas; Railia Karneta; Ida Aryani; Dewi Karnela (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2025)
This study aimed to determine the diversity of arthropods on peanut plants (Arachis hypogaea L.) grown on land treated with organic fertilizer. The research was conducted from July to December 2024 at Jalan Sukarela KM 7, Palembang City. Data collection for arthropods in the plant canopy was performed through direct observation, involving the counting and identification of arthropods visible on the surfaces of leaves and stems, without the use of nets. For soil surface observations, the pitfall trap method was employed. The observation parameters included the identification of arthropod types and the calculation of the diversity index at both the canopy and soil surface levels of the plants. Arthropods found in the peanut plant canopy belonged to 5 orders and 10 families, while those on the soil surface comprised 7 orders and 9 families. The diversity index in the plant canopy was 2.12, categorised as medium, whereas on the soil surface, it was 1.57, classified as low.